Beach Quality Evaluation as a Strategy for Sustainable Coastal Tourism Management - Kenedi Kenedi; April Laksana; Miftahul Huda (Postgraduate, University of Mataram, 2024)
This study evaluates the quality and visitor satisfaction across Anyer Beach, Tanjung Lesung Beach, Carita Beach, and Sawarna Beach in Banten, Indonesia, using the Bath Area Registration and Evaluation (BARE) survey and Importance-Performance (I-P) Matrix analysis. Each beach's attributes, including security, water quality, facilities, litter management, and scenery, are assessed to identify strengths and areas for improvement. The findings reveal varying levels of performance and visitor satisfaction, highlighting notable gaps in safety, medical facilities, showers, waste facilities, and changing rooms. Recommendations include enhancing safety measures, upgrading medical and shower facilities, improving waste management practices, and preserving scenic beauty to enhance visitor experiences and support sustainable tourism practices.